Analyzing the Share Composition of CO2 Emissions in Asian Countries - Cabalu, Helen; Inchauspe, Julian; Koshy, Paul (David Publishing Co, 2013)
This paper is concerned with the fossil fuel composition of carbon emissions in 10 selected Asian countries. It assesses how economic development may affect this composition through various channels. This paper contributes to the debate on the EKC (environmental Kuznets curve) puzzle, which hypothesizes an inverted U-shaped relationship between per capita income and pollution. The paper examines the EKC hypothesis in an empirical analysis of channels that may allow for this effect. In particular, a specific subset of this general paradigm is investigated using a fractional multinomial logit model to assess how indicators associated.